2003
DOI: 10.1097/00004770-200301000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Torsional and Bending Stresses in Two Mathematical Models of Nickel-Titanium Rotary Instruments: ProTaper versus ProFile

Abstract: During root canal instrumentation, nickel-titanium rotary instruments are subjected to continual stresses inside the canal due to its anatomy and the hardness of the dentin they must cut. They must therefore be both stress-resistant and elastic. This study aimed to compare the mechanical behavior of two nickel-titanium rotary instruments (ProTaper and ProFile) by applying the finite element analysis method to produce a numerical evaluation. The nonlinear mechanical behavior of the alloy was taken into account … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
172
2
23

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(208 citation statements)
references
References 15 publications
11
172
2
23
Order By: Relevance
“…Eğelerin kesit şeklinin stres dağılımını ve dolayısıyla torsiyonel ve eğilme davranışlarını etkilediği bildirilmiştir (14)(15)(16). Çalışmamızda eğri kök kanallarında şekillendirme esnasında oluşan streslerin belirlenmesi esas alındığı için farklı kesit, çap ve kesme açısına sahip bu iki sistem tercih edilmiştir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Eğelerin kesit şeklinin stres dağılımını ve dolayısıyla torsiyonel ve eğilme davranışlarını etkilediği bildirilmiştir (14)(15)(16). Çalışmamızda eğri kök kanallarında şekillendirme esnasında oluşan streslerin belirlenmesi esas alındığı için farklı kesit, çap ve kesme açısına sahip bu iki sistem tercih edilmiştir.…”
Section: Discussionunclassified
“…This shows us that these files are more feasible for apical transportation. Key words: Curved canals, HeroShaper, ProTaper, finite element analysis, stress MÜSBED 2013;3(1): [14][15][16][17][18] Araştırma / Original Paper GİRİŞ Kanal preparasyonunun temel amacı, kök kanal sistemini, organik artıklardan temizlemek ve tüm kök kanal boşlu-ğunu üç boyutlu ve hermetik bir şekilde doldurabilmek için şekillendirmektir (1). Eğri kök kanallarında şekillendirme işlemi sırasında, orijinal kanal seyrinin eğimin dış tarafına kayması sonucu kök kanal duvarının konkav kısmından kal-DOI: 10.5455/musbed.20130124112218 dırılamayan enfekte doku artıkları (2) ve bakteriler tedavinin başarısızlığına neden olabilmektedir.…”
Section: Introductionunclassified
“…There were a few reports about Mtwo rotary 11,18,19) , however, several researches have been studied for the safety and the efficiency of crown-down technique using ProTaper system [20][21][22] . The study using mathematic models have demonstrated that ProTaper instruments work longer in a super elastic phase than instruments with a Ufile design, allowing for high performance and less risk 20) . According to Calberson et al 21) , ProTaper instruments performed acceptable tapered preparations in all canal types.…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…Many studies have been conducted to compare the separation resistance and/or analyze the cause of separation of various NiTi instrument systems [12][13][14][15][16] . Some of the procedures used include the cyclic fatigue test 17) , the bending test 18,19) , differential scanning calorimetry 20) , and the nano-indentation test 21) .…”
Section: Introductionmentioning
confidence: 99%